2016
DOI: 10.1111/acer.13098
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Behavioral Responding in Adult and Aged Rats Following Chronic Ethanol Exposure

Abstract: The elderly may be vulnerable to EtOH withdrawal as modified-CIE aged rats displayed anxiety-like behavior compared to controls during withdrawal despite achieving lower blood EtOH concentrations during treatment than younger adults. Our data also indicate that modified-CIE and EtOH withdrawal cause persistent cognitive impairments in both age groups. The results from this study provide further evidence indicating the elderly may be sensitive to the effects of alcohol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 45 publications
(50 reference statements)
3
16
2
Order By: Relevance
“…In MWM, however, there was no effect of a history of alcohol drinking on latency to escape, suggesting that spatial learning was not affected by alcohol exposure. Previous studies demonstrating decreased MWM learning after alcohol exposure were in rats (Lukoyanov et al, 1999;Novier et al, 2016), and it is unclear why we did not observe these changes in this study, but species may be a factor. Besides species, the age of animals being studied is a potential factor.…”
Section: Chronic Voluntary Alcohol Drinking Induces Anxiety-like Behacontrasting
confidence: 74%
“…In MWM, however, there was no effect of a history of alcohol drinking on latency to escape, suggesting that spatial learning was not affected by alcohol exposure. Previous studies demonstrating decreased MWM learning after alcohol exposure were in rats (Lukoyanov et al, 1999;Novier et al, 2016), and it is unclear why we did not observe these changes in this study, but species may be a factor. Besides species, the age of animals being studied is a potential factor.…”
Section: Chronic Voluntary Alcohol Drinking Induces Anxiety-like Behacontrasting
confidence: 74%
“…Aged humans show differential GABA A receptor subunit expression (Kanaumi et al., ), have higher physiological sensitivity to alcohol (Menninger, ), and are more susceptible to the deficits associated with chronic AUD (Pfefferbaum et al., ). Further, aged animals show greater EtOH‐induced memory impairment and exhibit fewer withdrawal symptoms compared with adult animals (Novier et al., ), suggesting that aged adult individuals have unique responses to chronic EtOH exposure. In this study, we also show that 3α,5α‐THP concentrations are negatively correlated with age in amygdala regions, but not in the VTA and SNM regions.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were given a week off between tests to allow for recovery from multiple blood sampling. Since previous studies have reported age-related differences in EtOH pharmacokinetics at 3.0 g/kg but not 1.5 g/kg in males (Novier et al, 2016; Ornelas et al, 2015), we chose to examine BECs following several doses of EtOH. The low dose of EtOH was utilized previously in the test of social behavior (0.75 g/kg).…”
Section: Methodsmentioning
confidence: 99%
“…Altered behavior in response to EtOH in late aging could be due simply to age differences in EtOH pharmacokinetics and/or EtOH absorption and distribution. Indeed, there are some studies demonstrating impaired clearance of high doses of EtOH (3.0 g/kg) in 18-month-old Sprague-Dawley rats (Ornelas et al, 2015), although others have shown no age differences in BECs following acute administration of lower doses of EtOH (1.5–2.5 g/kg) (Matthews and Mittleman, 2017; Novier et al, 2016). All the aforementioned studies were performed exclusively in males.…”
Section: Introductionmentioning
confidence: 99%